Peer Tutoring Activities Implementation in Arabic Language Development at Indonesian Islamic Universities - Noor Hidayah, Selvi; Mustika Ilmiani, Aulia; Samdouni, Soukaina (Journal of Arabic Language Learning and Teaching (JALLT), 2024)
This study explores the utilization of peer tutoring activities to enhance Arabic language development in higher education, addressing challenges such as knowledge gaps and the lack of a conducive learning environment. Focusing on the Arabic Language Education Study Program at FTIK IAIN Palangka Raya, the research investigates the involvement of third and fifth-semester students in peer tutoring activities organized by HMPS PBA. Employing a qualitative approach, data collection involves interviews, observations, and documentation, with four Arabic tutors and lecturers serving as subjects and informants, respectively. Through analysis stages including data collection, reduction, presentation, and conclusion, the study examines the efficacy of peer tutoring in Arabic language learning. Findings reveal that tutors engage in preparatory steps, observation, and implementation to facilitate Arabic language development effectively. Students exhibit increased participation and enthusiasm, bolstering their confidence in learning Arabic. The research underscores the potential of peer tutoring to enhance Arabic language education in higher education settings, particularly within the Arabic Language Education Study Program at IAIN Palangka Raya.